Evaluation of Learning Media (Textbooks) in Area of Square and Rectangle to Prepare Student in Problem Solving: Praxeological Analysis - Rini Melani; Tatang Herman (PRISMA, 2023)
Textbooks are one of the learning media that need to be evaluated objectively because textbooks are a form of curriculum implementation that teachers usually use in the classroom. Many developed countries pay more attention to this study such as Japan, America, Holland, so textbook studies have been widely recognized as a field of scientific research. According to the Theory of Didactical Situations, the content of the material being taught must allow students to think. to make an objective analysis of the book, Researchers used Praxeology in this study. Praxeology, initiated by Chevallard, helps researchers see the reasons behind human action in textbooks and math. Based on the praxiological analysis, the result is that the design of the textbook does not provide techniques that facilitate students to acquire theory independently. In addition, the situations and actions students should go through need to be properly accommodated. This guides researchers to create alternative designs to provide meaningful learning experiences on broad flat material referring to the Theory of Didactic Situations.